Comparing Neonatal Pain Responses to Intravenous and Intramuscular Injections and Effect of Non- Pharmacological Measures - Dr. Pearl Mary Varughese,; Dr. Nandita Pai,; Dr. Prakash M., (International Journal of Innovative Research in Medical Science, 2021)
Background: Neonatal pain responses have been ignored for long, in spite of many pharmacological and non- pharmacological proven methods. Non pharmacological measures like breast feeding, non- nutritive sucking or glucose solutions are easily available, affordable and readily acceptable methods. Methods: 190 babies were compared for their responses to both intravenous pre discharge blood sampling and birth dose of hepatitis B vaccine. They were randomly divided into three groups - expressed breast milk (64 babies), 2ml 10% dextrose solution via syringe (63 babies), and non- nutritive sucking with 25% dextrose (63 babies). The response to each procedure was recorded in terms of cry duration and using NIPS scale. Kruskal Wallis test, Wilcoxon Signed Ranks test, Mann Whitney U test, ANOVA were used find the association between quantitative variables whereas McNemar test, McNemar-Bowker test and Chi-square test were used for qualitative variables. Results: The baseline demographic data of all the groups were comparable. The NIPS scores were reduced significantly in all the 3 groups in both the procedures. Babies on non-nutritive sucking with dextrose had the least scores, followed by babies on dextrose and finally those on expressed breast milk for both the procedures. All the 3 groups had significant variations in HR and SPO2 from baseline and at 3rd min, the variations were reducing with group 3 showing the maximum potential for quick stabilisation in both the procedures. The cry duration was significantly lower in group 3 in both the invasive procedures. Conclusion: Neonatal pain responses were least among the neonates provided with non- nutritive sucking with 25% dextrose during the intra-venous procedure and intra-muscular procedure. Non- nutritive sucking with 25% dextrose can be recommended as effective, reliable and useful method for decreasing the pain responses during the procedures.